Association between circulating big endothelin-1 and noncalcified or mixed coronary atherosclerotic plaques. Issue 6 (September 2019) - Wang, Fang; Li, Tiewei; Cong, Xiangfeng; Hou, Zhihui; Lu, Bin; Zhou, Zhou; Chen, Xi
Abstract : Background: Noncalcified plaques (NCPs) and mixed plaques (MPs) are considered as the high-risk coronary plaques. Endothelin-1 (ET-1) is a vasoactive peptide and shows a high expression in vulnerable plaque. The aim of this study is to investigate the relationship between the bigET-1, the precursor of ET-1, and NCPs/MPs in a Chinese population. Methods and results: A total of 513 patients with chest pain and suspected coronary artery disease were collected and divided into three groups with no plaques, calcified plaques, or NCPs/MPs according to the characteristics of all the plaques. It demonstrated that NCPs/MPs were associated with elevated bigET-1 ( P < 0.001). Moreover, the proportion of NCPs/MPs was significantly increased from 43.3% in bigET-1 tertile 1 to 61.0% in tertile 3 group ( P = 0.001). Multiple logistic regression analysis further showed that bigET-1 was an independent predictor for the presence of NCPs/MPs (odds ratio = 1.858; 95% confidence interval: 1.017–3.394; P = 0.044). Conclusion: The bigET-1 could be an independent predictor for the presence of NCPs/MPs. Abstract : Noncalcified plaques (NCPs) and mixed plaques (MPs) are considered as the high risk coronary plaques. Endothelin- 1(ET-1) is a vasoactive peptide and shows a high expression in vulnerable plaque. However, the relationship between circulating ET-1 and NCPs/MPs is still an unanswered question. In the present study, we found that NCPs and MPs were associated with elevated plasma bigET-1, the precursor of ET-1. The patients with NCPs and MPs had significantly elevated bigET-1, compared to those without coronary plaque or those have calcified plaques. Multiple logistic regression analysis further showed that bigET-1 was an independent predictor for the presence of NCPs/MPs. The finding highlights the potential value of this assay in predicting the characteristics of plaques in patients with suspected or known coronary artery disease.